Far-from-equilibrium dynamics of an ultracold Fermi gas - Kronenwett, Matthias; Gasenzer, Thomas (Applied physics. B, Lasers and optics, 2011)
Nonequilibrium dynamics of an N-fold spin-degenerate ultracold Fermi gas is described in terms of beyond-mean-field Kadanoff–Baym equations for correlation functions. Using a nonperturbative expansion in powers of 1/N, the equations are derived from the two-particle irreducible effective action in Schwinger–Keldysh formulation. The definition of the nonperturbative approximation on the level of the effective action ensures vital conservation laws as, e.g., for the total energy and particle number. As an example, the long-time evolution of a homogeneous, twofold spin-degenerate Fermi gas is studied in one spatial dimension after an initial preparation far from thermal equilibrium. Analysis of the fluctuation-dissipation relation shows that, at low energies, the gas does not thermalize.
Gesehen am 11.07.2022